The foundations of design and its impact on students' creativity (Journal of the College of Basic Education, 2022)
By examining the researcher with the literature and diagnosing the weaknesses of the curriculumThe course scheduled, whether by the students or the time allotted for the lecture, being the specialistIn interior design, there is a weakness in the use of design principles by students.In general, and in particular for the students of the Family Department, and the design of forms in terms of shapeMoreover, it does not express a single subject or is attributed to one of its categories.The researcher found that most of the students' outputs are limited to topics that are not consistent with the subject.The material because what pertains to the researcher is the external form of the artwork.2 Students' productions and works assigned to them lack the creative aspect. Most of the worksIt is implemented on the principle of repetition and even lack of coordination of design principles.techniques, the foundations of design did not obtain a portion of them and remained the same and creativity was not studied in itIn the implementation of works in university education on different materials and is limited to paperonly.3 Weakness in distinguishing, knowing, or discovering standards that bear the elements and design foundations inThe creative side, and the weakness may be in the lack of follow-up by the authorities responsible for teachingThis article uses the foundations of design. This prompted the researcher to define a topicResearch in teaching the subject of the foundations of design to reach creativity for students’ productsWhich he was guided to after extensive study and discussion with specialists.And personal experience determines the title of his tagged research (the foundations of design and its impact onrequest submissions).